Thermoelectric Properties of PEDOT/PSS-Halloysite Nanotubes (HNTs) Hybrid Films - Luo, Shi-Jun; Zhang, Ping; Mei, Yin-Ang; Chang, Jun-Biao; Ichikawa, Shoko; Oshima, Keisuke; Toshima, Naoki; Yan, Hu (Current Nanoscience, 2017)
Background: Recently it was for the first time found by us, that completely insulating Halloysite nanotubes significantly enhance electrical conductivity of PEDOT/PSS films by simply mixing. Based on this interesting finding highly porous and conductive PEDOT/PSS films hybridized with the Halloysite nanotubes (HNTs) were prepared. The highly porous morphology of the hybrid films would hinder thermal conduction, resulting in lower thermal conductivity which is an advantage for thermoelectric materials. Herein thermoelectric properties of the hybrid films are reported. Methods: The PEDOT/PSS-HNTs film was prepared using PEDOT/PSS dispersion containing 4wt% HNTs and 7wt% ethylene glycol (EG). The PEDOT/PSS-HNTs hybrid films were further treated with ammonium formate (AF) or poly(ethylene glycol) (PEG). The hybrid films were used for measurements of the thermoelectric performance. The electrical conductivity and Seebeck coefficient were measured by using a Ulvac ZEM-3 instrument while the thermal conductivity was measured with a Netzsch LFA 447/2-4/InSb NanoFlash TH Xe flash analyzer and with a Netzsch DSC 204F1 Phoenix differential analyzer, respectively. Results: The PEDOT/PSS-HNTs film, prepared using PEDOT/PSS dispersion containing 4wt% HNTs and 7wt% EG, had moderately high electrical conductivity and Seebeck coefficient, i.e., 46 S cm-1 and 19 μV K-1 at 300 K, respectively, coupled with a quite low thermal conductivity, i.e., 0.16 W m-1 K-1 at 300 K. On the other hand, the PEDOT/PSS-HNTs hybrid films treated with AF or PEG, also showed similar thermoelectric performance. Conclusion: All figure of merit (ZT) values of the hybrid films, which were calculated using corresponding electrical conductivity, Seebeck coefficient and thermal conductivity, were in the range of 1.3-5.5 x 10-3 at 300 K, comparable with those of conventional conducting polymers although the hybrid films composed of insulating HNTs in 75.5 wt%.
Keywords: Electrical conductivity